2003
DOI: 10.1039/b304195f
|View full text |Cite
|
Sign up to set email alerts
|

A scanning tunnelling microscopy insight into the preparation of carbon molecular sieves by chemical vapour deposition

Abstract: A direct visualization of the changes induced by chemical vapour deposition (CVD) on the micropore mouth structure of an activated carbon is provided by scanning tunnelling microscopy (STM). Micropore mouth narrowing after CVD treatment leading to an effective carbon molecular sieve (CMS) has been confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Such grooves are clearly observed in Figure 6 as dark, linear features running approximately parallel to the topbottom direction of the image. As discussed elsewhere, 38,42,44 these grooves, which are 1-2 nm wide, constitute the micropores of the ACF, since they are not seen on the carbonized material before activation (i.e., they develop upon activation) and their width reasonably agrees with the pore sizes of the sample as deduced from nitrogen physisorption data. Likewise, the observation of the micropores of the ACF as grooves is consistent with the micropore morphology of slit type expected for porous carbons prepared by activation.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Such grooves are clearly observed in Figure 6 as dark, linear features running approximately parallel to the topbottom direction of the image. As discussed elsewhere, 38,42,44 these grooves, which are 1-2 nm wide, constitute the micropores of the ACF, since they are not seen on the carbonized material before activation (i.e., they develop upon activation) and their width reasonably agrees with the pore sizes of the sample as deduced from nitrogen physisorption data. Likewise, the observation of the micropores of the ACF as grooves is consistent with the micropore morphology of slit type expected for porous carbons prepared by activation.…”
Section: Resultssupporting
confidence: 68%
“…35 STM, as a high-resolution imaging technique, allows a direct, real-space visualization of the local structure of carbon materials at scales not easily accessible by other techniques [36][37][38] and has in fact been formerly employed for the characterization of micro-and mesopo-rosity in activated carbons. [38][39][40][41][42] However, to the best of our knowledge, no STM studies on novel ordered porous carbons of any type have been previously reported, the work presented here constituting the first example in this regard. Likewise, as a complement to the STM data, Raman spectroscopy has been used to provide additional information on the microstructure and topology of the templated carbon.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Likewise, as a complementary characterization technique, STM plays an important role by providing a direct visualization of these materials at the nanometer scale . There are many examples in the literature on the application of STM to different types of porous carbons. For polyaramid-based ACFs, the STM studies have afforded an understanding of the basic structures responsible for their special adsorption behavior. , …”
Section: Porosity Characterization Of Polyaramid-based Carbonaceous M...mentioning
confidence: 99%
“…On the other hand, decomposition of volatile hydrocarbons at high temperature is used to deposit carbon in a well-defined manner as a so-called pyrolytic carbon or pyrocarbon on or in substrates. Microporous carbon molecular sieves have been successfully synthesized by CVD of volatile hydrocarbon or catalytic coke deposition (Kawabuchi et al 1996(Kawabuchi et al , 1997Prasetyo and Do 1999;Freitas and Figueiredo 2001;de la Casa-Lillo et al 2002;Villar-Rodil et al 2002, 2005Paredes et al 2003;David et al 2004;Carrott et al 2006) on microporous carbon materials.…”
mentioning
confidence: 99%